Efficiency of supercapacitor using EC/DMC-based liquid electrolytes with methyl methacrylate (MMA) monomer - Nadiah, N.S.; Mahipal, Y.K.; Numan, A.; Ramesh, S.; Ramesh, K. (Springer Verlag (Germany), 2016)
A liquid electrolyte based on binary solvent systems of ethylene carbonate (EC), dimethyl carbonate (DMC) and lithium bis(trifluoromethane)sulfonimide (LiTFSI) incorporated with methyl methacrylate (MMA) monomer is synthesized. The ionic conductivity (σ) ∼2.16 × 10−3 S cm−1 at room temperature is found for the 0.058 mol kg−1 of LiTFSI. Viscosity measurements are carried out within temperature ranges 25–40 °C. The activation energy Ea of the flow process (viscous flow) is calculated using Arrhenius equation. Structural properties of the liquid electrolyte are studied using Fourier transform infrared (FTIR) spectroscopy. Electrochemical supercapacitors are then assembled using the liquid electrolyte and activated carbons as electrode materials. The electrochemical properties of the supercapacitors are investigated using cyclic voltammetry, cyclic charge-discharge and electrochemical impedance spectroscopy techniques. It is found that the supercapacitors exhibited specific capacitance ∼46.5 F g−1 at 10 mV s−1. The long cycling stability of the supercapacitor containing monomer-based liquid electrolyte confirms the electrochemical stability of the electrolyte.